Perilaku Ekonomi Islami Perspektif Filsafat Sosial - Rozi, Muhammad Fachrur (JIOSE: Journal of Indonesian Sharia Economics, 2024)
This study seeks to provide a social philosophical (sociological) perspective on economic behaviour, moving past paradigmatic-methodological issues pertaining to an atomistic-individualistic pattern that sees human existence as merely an economic creature (homo economicus). This study obtains a philosophical explanation of related themes through descriptive-analytic methods. The data was inventoried from several reading sources (libraries) and analysed inductively to coherently produce a new paradigm regarding Islamic economic behaviour, which is conceptualised as 'amal iqtishâdiy, where this concept is read in the frame of social interaction, which is conceptualised as shilat al-rahim. This idea shows a change in perspective in understanding human existence from an individual one to an interactional one. Methodologically, there is a change from methodological individualism to methodological interactionism.